2023
DOI: 10.3934/mbe.2023315
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode dynamics and optimal control for HIV model

Abstract: <abstract><p>Considering the drug treatment strategy in both virus-to-cell and cell-to-cell transmissions, this paper presents an HIV model with Filippov control. Given the threshold level $ N_t $, when the total number of infected cells is less or greater than threshold level $ N_t $, the threshold dynamics of the model are studied by using the Routh-Hurwitz Criterion. When the total number of infected cells is equal to $ N_t $, the sliding mode equations are obtained by Utkin equivalent control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…With the development of research, Zhong et al [9] and Sattentau [10] revealed that HIV‐infected cells can transfer the virus to a target cell through a special structure known as a virological synapse. Subsequently, several researchers have begun working on HIV models that incorporate virus‐to‐cell and cell‐to‐cell transmissions [11–14]. These models are primarily based on ordinary differential equations (ODEs).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of research, Zhong et al [9] and Sattentau [10] revealed that HIV‐infected cells can transfer the virus to a target cell through a special structure known as a virological synapse. Subsequently, several researchers have begun working on HIV models that incorporate virus‐to‐cell and cell‐to‐cell transmissions [11–14]. These models are primarily based on ordinary differential equations (ODEs).…”
Section: Introductionmentioning
confidence: 99%